2005
DOI: 10.1167/iovs.04-0804
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Stromal Dystrophy of the Cornea Caused by a Mutation in the Decorin Gene

Abstract: The authors hypothesize that truncated decorin binds to collagen in a suboptimal way, disturbing the regularity of corneal collagen fibril formation and thereby causing corneal opacities. To the best of the authors' knowledge, this is the first description of a disorder associated with an inherited alteration in the decorin gene in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 22 publications
4
107
1
1
Order By: Relevance
“…The SLRP family consists of 17 member proteins that are largely characterized by the presence of N-terminal cysteine-rich clusters (33), and the exact role of SLRPs in vivo is poorly understood. It has been reported that they may regulate cell proliferation and differentiation in certain developmental contexts (33), and genetic mutations in decorin (DCN) and LUM have been implicated in inherited ocular disorders such as congenital stromal dystrophy and high myopia in the cornea (35,36). Our study suggests that SLRPs are novel regulators for smooth muscle differentiation.…”
Section: Discussionmentioning
confidence: 56%
“…The SLRP family consists of 17 member proteins that are largely characterized by the presence of N-terminal cysteine-rich clusters (33), and the exact role of SLRPs in vivo is poorly understood. It has been reported that they may regulate cell proliferation and differentiation in certain developmental contexts (33), and genetic mutations in decorin (DCN) and LUM have been implicated in inherited ocular disorders such as congenital stromal dystrophy and high myopia in the cornea (35,36). Our study suggests that SLRPs are novel regulators for smooth muscle differentiation.…”
Section: Discussionmentioning
confidence: 56%
“…SLRPs are involved in corneal stromal development, wound healing, and repair/remodeling and have been linked to several ocular abnormalities such as myopia 25 and cornea plana, 26 as well as CSCD. 4,5 Notably, decorin-null mice have clear corneas probably because of a functional compensation from upregulated biglycan. However, the double-mutant mice lacking both Dcn and Bgn genes show a severe stromal phenotype, which document decorin's central role in regulating fibrillogenesis in the corneal stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Patients develop early-onset corneal opacities and a disrupted stromal structure, indicating a novel role for decorin in regulating fibril organization. 4,6 Decorin is the prototype SLRP and contains a protein core and a single chondroitin/dermatan sulfate side chain covalently attached to Ser7 near the N-terminus. 7 The protein core has a central domain of tandem leucine-rich repeats (LRRs) flanked by conserved Cys-rich domains.…”
mentioning
confidence: 99%
“…Thinner stroma, decreased interfibrillar spacing, disorganized collagen arrangement; macular corneal dystrophy (Midura et al 1990;Hayashida et al 2006) Decorin Mild changes in collagen ultrastructure; congenital stromal dystrophy (Bredrup et al 2005;Zhang et al 2009 (Chaurasia et al 2013) Tenascin-C Upon corneal injury: delayed stromal wound healing, impaired keratocyte migration, fewer myofibroblasts, less invasion of macrophages, reduced expression of TGF-β (Matsuda et al 1999;Sumioka et al 2013) Proteoglycans are found associated with collagen fibrils in the corneal stroma; they have a core protein with one or more glycosaminoglycan (GAG) side chains covalently attached. Corneal proteoglycans mainly belong to the small leucine-rich type proteoglycan (SLRP) gene family and include decorin, biglycan, lumican, keratocan, mimecan and fibromodulin.…”
Section: Constituents Of Corneal Stromal Ecmmentioning
confidence: 99%